Properties and phase composition of cement mortars - L. N. Makarova; V. V. Schmidt; A. V. Ismagilova; V. V. Makarov (Архитектура, строительство, транспорт)
Introduction of complex antifreezes based on calcium formate, calcium chloride and superplasticizer Polyplast SP-1 into cement masses leads to changes in the phase composition of cement mortars. Of great importance are the developments of complex modifiers that are used for the hardening phase of cement-crushed mixtures, especially at low temperatures (down to –20 °C). The phase and structural characteristics of cement mortars have not been sufficiently studied. In this regard, the work investigated the effect of complex antifreeze additives on the properties and phase composition during the structuring of cement masses. Compressive strength reaches its maximum value (44.8 MPa) with the addition of calcium formate, calcium chloride and superplasticizer to the composition of cement pastes. X-ray diffraction analysis was carried out using a DRON-3 diffractometer. The used methods were standard. The X-ray diffraction patterns of the samples prove the high intensity of reflections of calcium hydrosilicate d = 9.69 Å, portlandite d = 4.921 Å, d = 2.632 Å, which indicates a high degree of hydration of portland cement. The combined use of calcium formate and calcium chloride promotes the activation of hydrolysis, and the addition of superplasticizer SP-1 leads to a decrease in the water-cement ratio to 0.20, which leads to an acceleration of the hardening process. Complex antifreeze additives increase the percentage ratio of crystalline phase to amorphous phase, thus, cement pastes with complex additives of 6 % (HCOO)2Ca, 3 % CaCl2, 2 % SP-1 have the highest value of degree of hydration (0.70) due to the formation of 63 % crystalline phase. Newly formed structures are typical for portlandite and dicalcium hydrosilicates. Complex antifreezes as an additive promote the activation of hydration in cement mortars, and the level of the degree of hydrolysis and the integral value of mass loss confirm this. Synergism of structure formation processes is observed at joint use of antifreeze additives in the composition of cement masses and, as a result, increases the strength of cement mortars used in construction at low climatic temperatures.